2015
DOI: 10.5380/cep.v33i1.43808
|View full text |Cite
|
Sign up to set email alerts
|

Composição Química E Susceptibilidade Do Óleo Essencial De Óregano (Origanum Vulgare L., Família Lamiaceae) Frente À Cepas De Escherichia Coli, Staphylococcus Aureus E Salmonella Choleraesuis

Abstract: condimentar que além de apresentar propriedades aromáticasapresenta também propriedades antimicrobianas e antioxidantes,que atuam como conservantes naturais inibindo o crescimentode micro-organismos. Este estudo teve como objetivo determinara composição química e avaliar a atividade antibacteriana doóleo essencial de orégano frente às cepas de Escherichia coli,Staphylococcus aureus e Salmonella choleraesuis. O métodoempregado para extração do óleo essencial de orégano foi dearraste de vapor d’água, utilizado o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
0
1
1
8
Order By: Relevance
“…Unlike our findings, Araújo et al (2015) identified 25 compounds in the oregano OE, with the two major ones being 4-terpineol and thymol, and with carvacrol not being detected as major compound. However, in the present study, samples of fresh oregano leaves were collected, while Araújo et al (2015) used dry leaves from the local market of São Luís, Maranhão. By assessing five commercial brands of oregano EO, Silva et al (2010) showed that the major component in all oils was carvacrol, corroborating our results.…”
Section: Resultscontrasting
confidence: 99%
“…Unlike our findings, Araújo et al (2015) identified 25 compounds in the oregano OE, with the two major ones being 4-terpineol and thymol, and with carvacrol not being detected as major compound. However, in the present study, samples of fresh oregano leaves were collected, while Araújo et al (2015) used dry leaves from the local market of São Luís, Maranhão. By assessing five commercial brands of oregano EO, Silva et al (2010) showed that the major component in all oils was carvacrol, corroborating our results.…”
Section: Resultscontrasting
confidence: 99%
“…Chromatography revealed that the essential oils of the analyzed species presented a diverse group of major compounds, some of which have been widely cited in the literature. According to Araújo et al (2015), the antibacterial action of essential oils is directly related to their chemical composition. Additionally, Millezi et al (2014) reinforced that, in Brazil, studies have described the existence of different chemical characteristics between the essential oils of the same species that are grown in different geographic regions of the globe.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos sugerem que as bactérias Gram-positivas são mais susceptíveis aos óleos essenciais, do que as Gram-negativas [3,23,24] . Isto ocorre provavelmente devido a complexidade estrutural da parede celular das Gram-negativas que apresentam uma membrana externa composta por lipopolissacarídeos, responsável por envolver a parede celular e proporcionar uma maior resistência, a qual restringe a difusão e dificulta a disseminação e acúmulo do óleo essencial na célula bacteriana [3,4,7,9,25] .…”
Section: Resultsunclassified